THE TRANSFORMATION OF THE ROLE OF PARENTS AND THE COMMUNITY AS STRATEGIC PARTNERS IN ACCELERATING THE QUALITY OF EDUCATION BASED ON LOCAL WISDOM AT SMAN 10 PANGKEP - Imrayani Imrayani; Kaharuddin Kaharuddin; Fatimah Azis (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the transformation of the role of parents and the community as strategic partners in accelerating the quality of education based on local wisdom at SMAN 10 Pangkep. The research uses a qualitative approach with a case study design. Data was collected through in-depth interviews, observations, and documentation involving principals, teachers, parents, community leaders, and students. Data analysis is carried out interactively through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that there is a shift in the role of parents and society from passive involvement to active and collaborative participation in supporting the educational process. Parents are involved in learning assistance, character strengthening, and participation in school programs based on local wisdom. The community plays a role as a source of contextual learning through the involvement of traditional and religious leaders in educational activities. Strategic partnerships built through participatory approaches, open communication, and the integration of local cultural values have been proven to contribute to improving the quality of education. Although still faced with obstacles such as limited parental time and unstructured partnership systems, strong local social and cultural capital is the main supporting factor in maintaining the sustainability of collaboration. This study concludes that the transformation of the role of parents and society based on local wisdom is an important foundation in the development of contextual, inclusive, and sustainable education.